The model of fracture development in the faulted folds: The role of folding and faulting. (January 2018) - Li, Yong; Hou, Guiting; Hari, K.R.; Neng, Yuan; Lei, Ganglin; Tang, Yangang; Zhou, Lu; Sun, Shuai; Zheng, Chunfang
Abstract: Tectonic fractures are otherwise known as joints or fissures. The density of tectonic fractures is governed by the lithology, layer thickness and structures. The distribution and density of tectonic fractures in the Kuqa Depression in the northern Tarim Basin of Northwest China are dominantly controlled by the regional faulted fold belt. Our purpose of this paper is to analyze how folding and faulting control the development of tectonic fractures, based on outcrop and logs of drill data. In the folded tight sandstone reservoirs in the Kuqa Depression, the extensional area, transition area and shortening area have been separated by two neutral lines, which control the distribution and density of tectonic fractures in the buckle folds. From the twelve sites of field measurements, six logs of drill core data and analysis of the micro-texture of tectonic fractures, it can be deduced that the fracture development in the sub-salt faulted fold belt is related to the neutral lines and related faults. The high-density tensile fractures in the vicinity of fold hinges are more developed than in the limbs of the fold. Folding is thus the first level of control over the general pattern of fracture distribution. The fractures in the hanging wall of the thrust faults are more developed than those in the footwall. Further more, the fractures in the hinge zone and steeply tilted limbs of folds close to thrust faults are more developed than the gently tilted limbs which are far from faulting. This suggests that faulting is a secondary control over the development of local fractures within the faulted fold belt. The development of fractures related to faulted folds in the Kuqa Depression can be also divided into three episodes: pre-folding, syn-folding and post-folding, which are identified by field observation. Graphical abstract: Highlights: The fracturing of faulted fold is controlled by the folding and faulting. The fracture areas in a fold can be divided into extensional, transition and shortening areas. The fracture densities are also related to the proximity to a fault.